Monthly labor review - United States. Bureau of Labor Statistics (Government Printing Office, 1918)
Publishes in-depth articles on labor subjects, current labor statistics, information about current labor contracts, and book reviews.
Keywords: Working class : United States : Periodicals; Working class : Periodicals; Labor supply : United States : Statistics : Periodicals; Labor laws and legislation : United States : Periodicals; Labor laws and legislation : Periodicals; Employment; Socioeconomic Factors; Classe ouvrière; Données statistiques; Droit du travail; Mensuels; Offre de main-d'oeuvre; Labor laws and legislation; Labor supply; Working class; Arbeid; United States; Etats-Unis d'Amérique; Verenigde Staten